Polyethylene Composition
Polyethylene compositions with defined density and melt index ranges and fraction ratios enhance stiffness and dart impact strength, addressing the need for cost-effective films with balanced properties.
Patent Information
- Application Number
- JP2024541048
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-01-13
- Publication Date
- 2025-01-24
AI Technical Summary
There is a need for polyethylene compositions that balance stiffness and performance properties, such as dart impact strength, while reducing material costs, particularly in film applications.
The development of polyethylene compositions with specific density and melt index ranges, incorporating a first and second polyethylene fraction defined by improved comonomer composition distribution (iCCD) analysis, which include a balanced ratio of these fractions to achieve desired stiffness and impact strength.
The compositions exhibit improved dart impact strength and stiffness, enabling reduced material costs through thinner film thicknesses without compromising performance.
Smart Images

Figure 2025502099000001_ABST
Abstract
Description
[Technical field]
[0001] FIELD OF THE DISCLOSURE
[0002] Embodiments described herein relate generally to polymer compositions, and more specifically to polyethylene compositions. [Background technology]
[0002] The use of polyolefin compositions in forming articles is generally known. Any conventional method can be adopted to produce such polyolefin compositions. Various polymerization techniques using different catalyst systems are used to produce such polyolefin compositions suitable for forming articles, such as films. Summary of the Invention
[0003] A variety of polymerization techniques using different catalyst systems are used to produce such polyolefin compositions suitable for the formation of articles, such as films, which may be used in packaging applications.
[0004] However, despite research efforts in developing compositions suitable for forming articles, there remains a need for compositions that have a balance of stiffness and performance properties that meet customer and industry demands. Furthermore, researchers are continually seeking solutions to enable material cost reduction, for example, by downgauging (i.e., using thinner film thicknesses) or by reducing or eliminating relatively expensive materials. Thus, there remains a need for compositions that have a balance of stiffness and performance properties that meet customer and industry demands.
[0005] The present disclosure is directed to a polyethylene composition that can exhibit desired stiffness while maintaining desired performance characteristics. For example, when used in a film, the present disclosure polyethylene composition can exhibit desired stiffness while maintaining desired dart impact strength. Thus, the present disclosure can provide a polyethylene composition that can enable material cost reduction due to the balance between stiffness and dart impact strength when utilized in the production of polymeric articles.
[0006] According to one or more embodiments, a polyethylene composition is provided. The polyethylene composition may include a first polyethylene fraction area defined by an area in a temperature range of 45°C to 90°C of an elution profile by an improved comonomer composition distribution (iCCD) analysis method, a first peak in a temperature range of 45°C to 90°C of the elution profile, a second polyethylene fraction area defined by an area in a temperature range of 90°C to 120°C of the elution profile, a second peak in a temperature range of 90°C to 120°C of the elution profile, and a minimum in a temperature range of 80°C to 95°C of the elution profile. The polyethylene composition may have a viscosity of 0.924 g / cm 3 ~0.936g / cm 3 and a melt index (I2) of 0.5 g / 10 min to 1.2 g / 10 min. The ratio of the area of the first polyethylene fraction to the area of the second polyethylene fraction may be from 2.0 to 4.0.
[0007] These and other embodiments are described in more detail below in the detailed description taken in conjunction with the accompanying drawings. [Brief description of the drawings]
[0008] The following detailed description of certain embodiments of the present disclosure can be best understood when read in conjunction with the following drawings, in which like structure is indicated with like reference numerals and in which:
[0009] [Figure 1]1 is a graph that generally illustrates an iCCD elution profile, according to one or more embodiments described herein. [Diagram 2] FIG. 1 illustrates a schematic of a reactor system useful for producing polyethylene according to one or more embodiments described herein. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Described herein are embodiments of polyethylene compositions. Such polyethylene compositions can be used, for example, in packaging applications. The polyethylene compositions can include a first polyethylene fraction and a second polyethylene fraction. The polyethylene compositions can be included in films (including monolayer and multilayer films) and other articles, such as multilayer structures and packaging materials. When utilized in articles such as films, a trade-off between tear strength (which may be correlated with overall density) and dart strength is often observed in conventional polyethylene materials. For example, higher density may provide higher tear strength but may reduce dart strength. However, in many end uses and products made from polyethylene, both good tear strength and dart strength are desirable. The embodiments of the polyethylene compositions described herein can provide good dart strength at relatively high density and provide a good balance of toughness with good tear strength.
[0011] Unless stated to the contrary, implied from the context, or customary in the art, all parts and percentages are by weight, all temperatures are in degrees Celsius, and all test methods are current as of the filing date of this disclosure.
[0012] As used herein, "polyethylene" or "ethylene-based polymer" refers to a polymer containing a majority (>50 mol%) of units derived from ethylene monomer. This includes polyethylene homopolymers or copolymers (meaning units derived from two or more comonomers). Common forms of polyethylene known in the art include low density polyethylene (LDPE), linear low density polyethylene (LLDPE), ultra low density polyethylene (ULDPE), very low density polyethylene (VLDPE), single-site catalyzed linear low density polyethylene (m-LLDPE), including both linear and substantially linear low density resins, ethylene-based plastomers (POP) and ethylene-based elastomers (POE), medium density polyethylene (MDPE), and high density polyethylene (HDPE). These polyethylene materials are generally known in the art. However, the following description may be helpful in understanding the differences between some of these different polyethylene resins.
[0013] As used herein, the term "composition" refers to a mixture of materials that comprise the composition, as well as reaction products and decomposition products formed from the materials of the composition.
[0014] The term "LDPE" may also be referred to as "high pressure ethylene polymer", or "highly branched polyethylene" and may be defined to mean that the polymer is partially or fully homopolymerized or copolymerized in an autoclave or tubular reactor at pressures in excess of 14,500 psi (100 MPa) using a free radical initiator, such as peroxide (see, for example, U.S. Pat. No. 4,599,392, incorporated herein by reference). LDPE resins typically have a viscosity of 0.916 to 0.935 g / cm. 3 The density is in the range of
[0015] The term "LLDPE" includes both resins made using traditional Ziegler-Natta catalyst systems and chromium-based catalysts, as well as single-site catalysts, including, but not limited to, mono- or bis-cyclopentadienyl catalysts (typically referred to as metallocenes), constrained geometry catalysts, phosphinimine catalysts and polyaryloxy ether catalysts (typically referred to as bisphenylphenoxy), and includes linear, substantially linear, or heterogeneous polyethylene copolymers or homopolymers. LLDPE contains less long chain branching than LDPE and includes substantially linear ethylene polymers, as further defined in U.S. Patents 5,272,236, 5,278,272, 5,582,923, and 5,733,155; homogeneously branched linear ethylene polymer compositions such as those in U.S. Patent 3,645,992, heterogeneously branched ethylene polymers such as those prepared according to the process disclosed in U.S. Patent 4,076,698, and / or blends thereof (such as those disclosed in U.S. Patents 3,914,342 or 5,854,045). LLDPE may be made via gas phase, solution phase, or slurry polymerization, or any combination thereof, using any type of reactor or reactor configuration known in the art.
[0016] The term "MDPE" means 0.924 g / cm 3 ~0.936g / cm 3"MDPE" refers to polyethylene having a density of 100 to 2000 nm. "MDPE" is typically made using chromium or Ziegler-Natta catalysts, or using single-site catalysts, including, but not limited to, substituted mono- or bis-cyclopentadienyl catalysts (typically referred to as metallocenes), constrained geometry catalysts, phosphinimine catalysts, and polyaryloxy ether catalysts (typically referred to as bisphenylphenoxy).
[0017] The term "HDPE" refers to any polymer having a viscosity of about 0.936 g / cm, typically prepared using single-site catalysts, including, but not limited to, Ziegler-Natta, chromium, or substituted mono- or bis-cyclopentadienyl catalysts (typically referred to as metallocenes), constrained geometry catalysts, phosphinimine catalysts, and polyaryloxy ether catalysts (typically referred to as bisphenylphenoxy). 3 Super ~ maximum approx. 0.980g / cm 3 It refers to polyethylene having a density of
[0018] The term "ULDPE" refers to poly(ethylene glycol) copolymers (ULDPE) having a viscosity of 0.855 to 0.912 g / cm, typically prepared using single-site catalysts including, but not limited to, Ziegler-Natta, chromium, or substituted mono- or bis-cyclopentadienyl catalysts (typically referred to as metallocenes), constrained geometry catalysts, phosphinimine catalysts, and polyaryloxy ether catalysts (typically referred to as bisphenylphenoxy). 3 ULDPE refers to polyethylene having a density of 0.855 to 0.912 g / cm. Examples of ULDPE include, but are not limited to, polyethylene (ethylene-based) plastomers and polyethylene (ethylene-based) elastomers. Polyethylene (ethylene-based) elastomers or plastomers generally have a density of 0.855 to 0.912 g / cm. 3 has a density of
[0019] "Blend", "polymer blend" and similar terms refer to a composition of two or more polymers. Such blends may or may not be miscible. Such blends may or may not be phase separated. Such blends may or may not contain one or more domain configurations as determined from transmission electron spectroscopy, light scattering, X-ray scattering, and any other method known in the art. A blend is not a laminate, although one or more layers of a laminate may contain the blend. Such blends may be prepared as dry blends formed in situ (e.g., in a reactor), as melt blends, or using other techniques known to those skilled in the art.
[0020] The terms "comprising," "including," "having," and their derivatives are not intended to exclude the presence of any additional components, steps, or procedures, whether or not they are specifically disclosed. For the avoidance of any doubt, all compositions claimed through the use of the term "comprising" may include any additional additives, adjuvants, or compounds, whether polymeric or otherwise, unless otherwise stated to the contrary. In contrast, the term "consisting essentially of" excludes from the scope of any succeeding description any other component, step, or procedure, except those that are not essential to operability. The term "consisting of" excludes any component, step, or procedure not specifically delineated or listed.
[0021] Polyethylene composition and characterization
[0022] In one or more embodiments, the polyethylene composition has a viscosity of 0.924 g / cm 3 ~0.936g / cm 3 For example, an embodiment of the polyethylene composition of the present disclosure may have a density of 0.924 g / cm 3 ~0.934g / cm 3, 0.924g / cm 3 ~0.932g / cm 3 , 0.924g / cm 3 ~0.930g / cm 3 , 0.924g / cm 3 ~0.928g / cm 3 , 0.924g / cm 3 ~0.926g / cm 3 , 0.926g / cm 3 ~0.936g / cm 3 , 0.926g / cm 3 ~0.934g / cm 3 , 0.926g / cm 3 ~0.932g / cm 3 , 0.926g / cm 3 ~0.930g / cm 3 , 0.926g / cm 3 ~0.928g / cm 3 , 0.928g / cm 3 ~0.936g / cm 3 , 0.928g / cm 3 ~0.934g / cm 3 , 0.928g / cm 3 ~0.932g / cm 3 , 0.928g / cm 3 ~0.930g / cm 3 , 0.930g / cm 3 ~0.936g / cm 3 , 0.930g / cm 3 ~0.934g / cm 3 , 0.930g / cm 3 ~0.932g / cm 3 , 0.932g / cm 3 ~0.936g / cm 3 , 0.932g / cm 3 ~0.934g / cm 3 , 0.934g / cm 3 ~0.936g / cm 3 , or any combination of these ranges.
[0023] In one or more embodiments, the polyethylene composition may have a melt index (I2) of 0.50 g / 10 min to 1.2 g / 10 min. For example, in one or more embodiments, the polyethylene composition may have a melt index (I2) of 0.5 g / 10 min to 1.0 g / 10 min, 0.5 g / 10 min to 0.8 g / 10 min, 0.5 g / 10 min to 0.6 g / 10 min, 0.6 g / 10 min to 1.2 g / 10 min, 0.6 g / 10 min to 1.0 g / 10 min, 0.6 g / 10 min to 0.8 g / 10 min, 0.8 g / 10 min to 1.2 g / 10 min, 0.8 g / 10 min to 1.0 g / 10 min, 1.0 g / 10 min to 1.2 g / 10 min, or any combination of these ranges.
[0024] According to one or more additional embodiments, the polyethylene composition may have a zero shear viscosity ratio of less than 3.0. For example, the polyethylene composition may have a zero shear viscosity ratio of less than 2.9, less than 2.8, less than 2.7, less than 2.6, less than 2.5, less than 2.4, less than 2.3, less than 2.2, less than 2.1, less than 2.0, less than 1.9, less than 1.8, less than 1.7, less than 1.6, less than 1.5, less than 1.4, less than 1.3, less than 1.2, or even less than 1.1. In one or more embodiments, the polyethylene composition may have a zero shear viscosity ratio of at least 1.0.
[0025] According to an embodiment, the polyethylene composition may have a molecular weight distribution, expressed as the ratio of weight average molecular weight to number average molecular weight (Mw / Mn), in the range of 2.5 to 8.0. For example, the polyethylene composition may have a molecular weight distribution of 2.5 to 7.0, 2.5 to 6.0, 2.5 to 5.0, 2.5 to 4.0, 2.5 to 3.0, 3.0 to 8.0, 3.0 to 7.0, 3.0 to 6.0, 3.0 to 5.0, 3.0 to 4.0, 4.0 to 8.0, 4.0 to 7.0, 4.0 to 6.0, 4.0 to 5.0, 5.0 to 8.0, 5.0 to 7.0, 5.0 to 6.0, 6.0 to 8.0, 6.0 to 7.0, or 7.0 to 8.0, or any combination of these ranges. In an additional embodiment, the polyethylene composition may have a molecular weight distribution of 3.0 to 5.0. As described herein, the molecular weight distribution may be calculated according to gel permeation chromatography (GPC) techniques as described herein.
[0026] As described herein, a polyethylene "fraction" refers to a portion of the overall composition of a multimodal polyethylene composition. An embodiment of the present disclosure includes at least a "first polyethylene fraction" and a "second polyethylene fraction." The various fractions contained in the polyethylene composition may be quantified by their temperature ranges in the elution profile by improved comonomer composition distribution (iCCD) analysis. Unless otherwise specified, any elution profile referred to herein is an elution profile observed by iCCD. Examples of such fractions will be better understood in view of the examples provided herein. In general, the first fraction may include a peak within the temperature range of the first fraction and the second fraction may include a peak within the temperature range of the second fraction. The polyethylene compositions described herein may be referred to as "multimodal," meaning that the polyethylene compositions include at least two peaks in their elution profile. Some embodiments may be "bimodal," meaning that there are two major peaks.
[0027] With reference to the iCCD distributions described, FIG. 1 shows a schematic of the iCCD distribution 100 of a sample along with a cumulative weight fraction curve 200. FIG. 1 generally shows several features of the iCCD profile of the polyethylene composition described herein, such as the first fraction, the second fraction, and the half-peak width, as discussed in detail herein. Thus, FIG. 1 may be used as a reference with respect to the disclosure related to the iCCD profile provided herein. Specifically, a first fraction 102 and a second fraction 106 are illustrated. The first fraction 102 has a peak 104, and the second fraction 106 has a peak 108. Each fraction has a half-peak width 110 and 112. There is a local minimum 111 between the peaks 104 and 108. It should be understood that the profile in FIG. 1 is not derived from experiment or observation, but is instead provided for informational purposes to describe certain features of the iCCD elution profile.
[0028] In one or more embodiments, the polyethylene composition may have a first polyethylene fraction area defined by the area of an improved comonomer composition distribution (iCCD) elution profile within the temperature range of 45° C. to 90° C. The first polyethylene area fraction may correspond to the total relative mass of the polymer fractions in the polyethylene composition, sometimes referred to herein as the “first mass fraction.”
[0029] In embodiments, the first polyethylene fraction may have at least one peak in the temperature range of 45°C to 90°C of the iCCD elution profile. In some embodiments, the first polyethylene fraction area may encompass the area in the elution profile under the peak in the temperature range of 45°C to 90°C of the iCCD elution profile. In further embodiments, the first polyethylene fraction may have a single peak in the temperature range of 45°C to 90°C of the iCCD elution profile. As used herein, "single peak" refers to an iCCD in which a particular fraction contains only one peak. That is, in some embodiments, the iCCD of the first polyethylene fraction contains only an upward sloping region followed by a downward sloping region to form a single peak. In one or more embodiments, the single peak of the first polyethylene fraction may be in the temperature range of 45°C to 90°C, such as 45°C to 85°C and 45°C to 80°C.
[0030] It should be understood that the peak in the first polyethylene fraction may not be formed by a local minimum in the respective polyethylene fraction at a defined temperature boundary. That is, the peak should be a peak in terms of the entire range, not a peak formed by a threshold temperature of the polyethylene fraction. For example, if there is a single peak in the polyethylene fraction followed by a single valley (upward slope followed by downward slope followed by upward slope), then there will be only a single peak in such polyethylene fraction.
[0031] In one or more embodiments, the first polyethylene fraction area may comprise more than 50% of the total area of the elution profile (e.g., more than 55% or more than 60% of the total area of the elution profile). For example, the first polyethylene fraction area may comprise 50%-90% of the total area of the elution profile, such as 50%-80%, 50%-70%, 50%-60%, 60%-90%, 60%-80%, 60%-70%, 70%-90%, 70%-80%, 80%-90% of the total area of the elution profile.
[0032] In one or more embodiments, the polyethylene composition may have a second polyethylene fraction area within a temperature range of 90° C. to 120° C. of an elution profile by improved comonomer composition distribution (iCCD) analysis. As used herein, the second polyethylene fraction area may be defined as the area in the elution profile under the second polyethylene fraction from 90° C. to 120° C. The area fraction of the second polyethylene may correspond to the total relative mass of the polymer fraction in the polyethylene composition, referred to herein as the "second mass fraction."
[0033] In one or more embodiments, the second polyethylene fraction may have a single peak within the temperature range of 90°C to 120°C of the iCCD elution profile. It should be understood that the peak in the second polyethylene fraction may not be formed by a local minimum in the respective polyethylene fraction at a defined temperature boundary. That is, the peak must be in terms of the entire range, not a peak formed by a threshold temperature of the polyethylene fraction. For example, if there is a single peak in the polyethylene fraction followed by a single valley (upward slope followed by downward slope followed by upward slope), then there will only be a single peak in such polyethylene fraction. A temperature range of 90°C to 120°C for the second polyethylene fraction may be desirable because the low molecular weight, high density components at 90°C to 120°C allow the polyethylene to achieve a higher overall density while maintaining a lower density fraction.
[0034] According to one or more embodiments, the second polyethylene fraction area may comprise 50% or less of the total area of the elution profile (e.g., 40% or less, 45% or less, or 30% or less of the total area of the elution profile). For example, the second polyethylene fraction area may comprise 10%-50%, 10%-40%, 10%-30%, 10%-20%, 20%-50%, 20%-40%, 20%-30%, 30%-50%, 30%-40%, or 40%-50% of the total area of the elution profile.
[0035] In one or more embodiments, the width at 50 percent peak height of the single peak of the second polyethylene fraction may be less than 10.0° C., less than 8.0° C., less than 6.0° C., less than 4.0° C., or even less than 2° C. In general, a smaller temperature range at 50 percent peak height corresponds to a "sharper" peak. Without being bound to any particular theory, it is believed that a "sharper" or "narrower" peak is a characteristic caused by molecular catalysis, indicating minimal comonomer incorporation in the higher density fraction, allowing for higher density partitioning between the two fractions.
[0036] In one or more embodiments, the polyethylene composition may have a minimum or "trough" in a temperature range of 80° C. to 95° C., 80° C. to 90° C., 80° C. to 85° C., 85° C. to 95° C., 85° C. to 90° C., or 90° C. to 95° C., or any combination of these ranges, in an iCCD elution profile. The minimum may fall between the peak of the first polyethylene fraction and the peak of the second polyethylene fraction.
[0037] According to one or more embodiments, the difference between the temperature of the single peak of the second polyethylene fraction and the temperature of the single peak of the first polyethylene fraction may be at least 10° C. For example, the difference between the temperature of the single peak of the second polyethylene fraction and the single peak of the first polyethylene fraction may be at least 12° C., 14° C., 16° C., 18° C., or even at least 20° C.
[0038] According to some embodiments, the ratio of the first polyethylene fraction area to the second polyethylene fraction area can be from 2.0 to 4.0, 2.0 to 3.5, 2.0 to 3.0, 2.0 to 2.5, 2.5 to 4.0, 2.5 to 3.5, 2.5 to 3.0, 3.0 to 4.0, 3.0 to 3.5, 3.5 to 4.0, or any combination of these ranges.
[0039] In one or more embodiments, the polyethylene composition is formed from the polymerization of ethylene and a comonomer, such as a C3-C12 alkene. Contemplated comonomers include C6-C9 alkenes, such as 1-octene and 1-hexene. In one or more embodiments, the comonomer is 1-octene.
[0040] In one or more embodiments, the first polyethylene fraction may have a melt index (I2) of 0.01 to 0.18 g / 10 min. For example, according to one or more embodiments, the first polyethylene fraction may have a melt index (I2) of 0.01 g / 10 min to 0.03 g / 10 min, 0.03 g / 10 min to 0.05 g / 10 min, 0.05 g / 10 min to 0.07 g / 10 min, 0.07 g / 10 min to 0.09 g / 10 min, 0.09 g / 10 min to 0.11 g / 10 min, 0.11 g / 10 min to 0.13 g / 10 min, 0.13 g / 10 min to 0.15 g / 10 min, 0.15 g / 10 min to 0.18 g / 10 min, or any combination of these ranges.
[0041] In one or more embodiments, the second polyethylene fraction may have a melt index (I2) of 1 to 10,000 g / 10 min. For example, according to one or more embodiments, the second polyethylene fraction may have a melt index (I2) of 10 g / 10 min to 1,000 g / 10 min, 20 g / 10 min to 800 g / 10 min, 1 g / 10 min to 100 g / 10 min, 100 g / 10 min to 1,000 g / 10 min, 1,000 g / 10 min to 10,000 g / 10 min, or any combination of these ranges.
[0042] In one or more embodiments, the weight average molecular weight of the second polyethylene fraction can be 100,000 g / mol or less, e.g., from 20,000 g / mol to 100,000 g / mol, or from 40,000 g / mol to 65,000 g / mol. In additional embodiments, the weight average molecular weight of the second polyethylene fraction can be from 20,000 g / mol to 40,000 g / mol, from 40,000 g / mol to 60,000 g / mol, from 60,000 g / mol to 80,000 g / mol, from 80,000 g / mol to 100,000 g / mol, or any combination of ranges thereof. The molecular weight of the polyethylene fraction can be calculated based on GPC results, as described herein below.
[0043] The polyethylene compositions described herein may have relatively good dart strength when formed into monolayer blown films. According to one or more embodiments, a monolayer blown film formed from the polyethylene composition and having a thickness of 2 mils has a dart drop impact of at least 1000 grams, as measured according to ASTM D1709, Method A. In additional embodiments, a monolayer blown film formed from the polyethylene composition and having a thickness of 2 mils has a dart drop impact of at least 1100 grams, at least 1200 grams, at least 1300 grams, at least 1400 grams, at least 1500 grams, at least 1600 grams, at least 1700 grams, at least 1800 grams, at least 1900 grams, or even at least 2000 grams, as measured according to ASTM D1709, Method A.
[0044] In one or more embodiments, the polyethylene composition of the present disclosure may further comprise additional components such as one or more additives. Such additives include, but are not limited to, antistatic agents, color enhancers, dyes, lubricants, fillers such as TiO2 or CaCO3, opacifiers, nucleating agents, processing aids, pigments, primary antioxidants, secondary antioxidants, UV stabilizers, antiblocking agents, slip agents, tackifiers, flame retardants, antimicrobial agents, odor reducing agents, antifungal agents, and combinations thereof. The polyethylene composition may contain from about 0.1 to about 10 weight percent of such additives by combined weight, based on the weight of the polyethylene composition including such additives.
[0045] polymerization
[0046] Any conventional polymerization process may be used to produce the polyethylene compositions described herein. Such conventional polymerization processes include, but are not limited to, slurry polymerization processes, solution polymerization processes using one or more conventional reactors, such as loop reactors, isothermal reactors, stirred tank reactors, parallel, continuous batch reactors, and / or any combination thereof. The polyethylene compositions may be produced, for example, via a solution phase polymerization process using one or more loop reactors, isothermal reactors, and combinations thereof.
[0047] Generally, the solution phase polymerization process may be carried out in one or more well-stirred reactors, such as one or more isothermal loop reactors or one or more adiabatic reactors, at temperatures ranging from 115 to 250° C. (e.g., 115 to 210° C.) and pressures ranging from 300 to 1,000 psi (e.g., 400 to 800 psi). In some embodiments, in a dual reactor, the temperature in the first reactor is in the range of 115 to 190° C. (e.g., 160 to 180° C.) and the temperature in the second reactor is in the range of 150 to 250° C. (e.g., 180 to 220° C.). In other embodiments, in a single reactor, the reactor temperature is in the range of 115 to 250° C. (e.g., 115 to 225° C.).
[0048] The residence time in the solution phase polymerization process can be in the range of 2 to 30 minutes (e.g., 5 to 25 minutes). Ethylene, solvent, hydrogen, one or more catalyst systems, optionally one or more cocatalysts, and optionally one or more comonomers are continuously fed to one or more reactors. Exemplary solvents include, but are not limited to, isoparaffins. For example, such solvents are commercially available under the name ISOPAR E from ExxonMobil Chemical Co. (Houston, Texas). The resulting mixture of polyethylene composition and solvent is then removed from the reactor and the polyethylene composition is isolated. The solvent is typically recovered via a solvent recovery unit, such as a heat exchanger and a gas-liquid separator drum, and then recycled to the polymerization system.
[0049] In some embodiments, the polyethylene composition can be produced by solution polymerization in a dual reactor system, e.g., a dual loop reactor system, where ethylene is polymerized in the presence of one or more catalyst systems. In some embodiments, only ethylene is polymerized. In addition, one or more cocatalysts can be present. In another embodiment, the polyethylene composition can be produced by solution polymerization in a single reactor system, e.g., a single loop reactor system, where ethylene is polymerized in the presence of two catalyst systems. In some embodiments, only ethylene is polymerized.
[0050] Catalyst system
[0051] Common abbreviations are listed below.
[0052] Me: methyl, Et: ethyl, Ph: phenyl, Bn: benzyl, i-Pr: iso-propyl, t-Bu: tert-butyl, t-Oct: tert-octyl (2,4,4-trimethylpentan-2-yl), Tf: trifluoromethanesulfonate, THF: tetrahydrofuran, Et2O: diethyl ether, CH2Cl2: dichloromethane, CV: column volume (if used in column chromatography), EtOAc: ethyl acetate, C6D6: deuterated benzene or benzene-d6, CDCl3: deuterated chloroform, Na2SO4: sodium sulfate, MgSO4: magnesium sulfate, HCl: hydrogen chloride, n-BuLi: butyl lithium, t-BuLi: tert-butyl lithium, MAO: methylaluminoxane, MMAO: modified methylaluminoxane, GC: gas chromatography, LC: liquid chromatography, NMR: nuclear magnetic resonance, MS: mass spectrometry, mmol: millimole, mL: milliliter, M: molar concentration, min or mins: minutes, h or hrs: hours, d: days.
[0053] Described herein are specific embodiments of catalyst systems that can be used in one or more embodiments to produce the polyethylene compositions described herein. It is understood that the catalyst systems of the present disclosure may be embodied in different forms and should not be construed as being limited to the specific embodiments described in this disclosure. Rather, the embodiments are provided so that this disclosure will be thorough and complete, and will fully convey the scope of the subject matter to those skilled in the art.
[0054] The term "independently selected" means 1 , R 2 , R 3 , R 4 , and R 5 The R groups, such as R 1 , R 2 , R 3 , R 4 , and R 5 may all be substituted alkyl, or R 1 and R 2 may be substituted alkyl, R 3R may be aryl, etc. Chemical names associated with R groups are intended to convey chemical structures that are recognized in the art as corresponding to the chemical structure of the chemical name. Thus, the chemical names are intended to supplement and illustrate, not preclude, structural definitions known to those of skill in the art.
[0055] The term "procatalyst" refers to a transition metal compound that has olefin polymerization catalytic activity when combined with an activator. The term "activator" refers to a compound that chemically reacts with the procatalyst to convert it into a catalytically active catalyst. As used herein, the terms "cocatalyst" and "activator" are interchangeable terms.
[0056] When used to describe a chemical group that contains a particular carbon atom, "(C x ~C y A bracketed expression having the form "(C1-C)" means that the unsubstituted form of the chemical group has from x carbon atoms to y carbon atoms, inclusive of x and y. For example, (C1-C 50 ) Alkyl is an alkyl group having 1 to 50 carbon atoms in its unsubstituted form. In some embodiments and general structures, certain chemical groups are R S The parenthetical "(C x ~C y )" S The substituted chemical group can be any group R S For example, "R S Exactly one group R is phenyl (-C6H5) S (C1~C 50 "(C)alkyl" can contain from 7 to 56 carbon atoms. Thus, the parenthetical "(C)alkyl" is generally used. x ~C y )" is a substituent R SWhen a chemical group is substituted by x, the minimum and maximum total number of carbon atoms in the group is determined by the presence of both x and y in the substituent R S It is determined by adding the total number of carbon atoms from
[0057] The term “substituted” refers to at least one hydrogen atom (—H) bonded to a carbon atom of the corresponding unsubstituted compound or functional group, replaced by a substituent (e.g., R S The term "-H" means a hydrogen or hydrogen radical that is covalently bonded to another atom. "Hydrogen" and "-H" are interchangeable and have the same meaning unless otherwise specified.
[0058] "(C1~C 50 The term "(C1-C)alkyl" means a saturated linear or branched hydrocarbon radical containing 1 to 50 carbon atoms. 30 The term "alkyl" means a saturated linear or branched hydrocarbon radical of 1 to 30 carbon atoms. 50 ) alkyl and (C1-C 30 ) Alkyl can be unsubstituted or can have one or more R S In some instances, each hydrogen atom in a hydrocarbon radical can be substituted with R, such as trifluoromethyl. S Can be substituted with unsubstituted (C1-C 50 Examples of alkyl are unsubstituted (C1-C 20 ) Alkyl, unsubstituted (C1-C 10 ) alkyl, unsubstituted (C1-C5) alkyl, methyl, ethyl, 1-propyl, 2-propyl, 1-butyl, 2-butyl, 2-methylpropyl, 1,1-dimethylethyl, 1-pentyl, 1-hexyl, 1-heptyl, 1-nonyl, and 1-decyl. 40 Examples of substituted (C1-C 20 ) Alkyl, Substituted (C1-C 10 ) alkyl, trifluoromethyl, and [C 45 ] alkyl. 45The term "alkyl" means that there are up to 45 carbon atoms in the radical, including the substituents, and includes one R which is (C1-C5) alkyl, such as methyl, trifluoromethyl, ethyl, 1-propyl, 1-methylethyl, or 1,1-dimethylethyl. S is replaced by (C 27 ~C 40 ) alkyl.
[0059] (C3~C 50 The term alkenyl refers to an alkyl group containing 3 to 50 carbon atoms, at least one double bond, and is unsubstituted or has one or more R S means a branched or unbranched, cyclic or acyclic monovalent hydrocarbon radical, substituted with unsubstituted (C3-C 50 ) Examples of alkenyl: n-propenyl, isopropenyl, n-butenyl, isobutenyl, octenyl, decenyl, cyclopentenyl, cyclopentadienyl, cyclohexenyl, and cyclohexadienyl. Substituted (C3-C 50 Examples of alkenyl are (2-trifluoromethyl)pent-1-enyl, (3-methyl)hex-1-enyl, (3-methyl)hexa-1,4-dienyl, and (Z)-1-(6-methylhept-3-en-1-yl)cyclohex-1-enyl.
[0060] "(C3~C 50 The term "cycloalkyl" refers to an unsubstituted or substituted cycloalkyl group. S means a saturated cyclic hydrocarbon radical of 3 to 50 carbon atoms, substituted with other cycloalkyl groups, such as (C x ~C y )Cycloalkyl) has x to y carbon atoms and is unsubstituted or has one or more R S Unsubstituted (C3-C 40 Examples of cycloalkyl are unsubstituted (C 20 )Cycloalkyl, unsubstituted (C3-C 10) cycloalkyl, cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl, cyclononyl, and cyclodecyl. 40 Examples of cycloalkyl are substituted (C3-C 20 )Cycloalkyl, substituted (C3-C 10 ) cycloalkyl, and 1-fluorocyclohexyl.
[0061] The term "halogen atom" or "halogen" refers to a radical of a fluorine atom (F), a chlorine atom (Cl), a bromine atom (Br), or an iodine atom (I). The term "halide" refers to the anionic form of a halogen atom, fluoride (F - ), chloride (Cl - ), bromide (Br - ), or iodide (I - )
[0062] The term "saturated" means lacking carbon-carbon double bonds, carbon-carbon triple bonds, and (in heteroatom-containing groups) carbon-nitrogen double bonds, carbon-phosphorus double bonds, and carbon-silicon double bonds. A saturated chemical group is one or more substituents R S When substituted by, one or more double or triple bonds may optionally be replaced by a substituent R S The term "unsaturated" refers to a group containing one or more carbon-carbon double bonds or carbon-carbon triple bonds, or (in heteroatom-containing groups) one or more carbon-nitrogen double bonds, carbon-phosphorus double bonds, or carbon-silicon double bonds, and may be present in the substituent R S (if present), or in an aromatic or heteroaromatic ring (if present).
[0063] "(C1~C 40 The term "(C1-C)hydrocarbyl" means a hydrocarbon radical of 1 to 40 carbon atoms. 40The term "hydrocarbylene" means a hydrocarbon diradical of 1 to 40 carbon atoms, each of which may be aromatic or non-aromatic, saturated or unsaturated, straight or branched chain, cyclic (including monocyclic and polycyclic, fused and non-fused polycyclic, including bicyclic, 3 or more carbon atoms) or acyclic, unsubstituted or substituted with one or more R S has been replaced by
[0064] In the present disclosure, (C1 to C 40 ) Hydrocarbyl is unsubstituted or substituted (C1-C 40 ) Alkyl, (C3-C 40 )Cycloalkyl, (C3-C 20 )Cycloalkyl-(C1-C 20 ) Alkylene, (C6-C 40 ) aryl, or (C6-C 20 )Aryl-(C1-C 20 In some embodiments, the above (C1-C 40 Each of the hydrocarbyl groups has up to 20 carbon atoms (i.e., (C1-C 20 ) hydrocarbyl), in embodiments having up to 12 carbon atoms.
[0065] "(C6~C 40 The term "aryl" refers to an unsubstituted or substituted aryl group having 6 to 40 carbon atoms, of which at least 6 to 14 carbon atoms are aromatic ring carbon atoms. S means a monocyclic, bicyclic, or tricyclic aromatic hydrocarbon radical substituted (by C6-C 40 Examples of aryl are unsubstituted (C6-C 20 )Aryl unsubstituted (C6-C 18)aryl, 2-(C1-C5)alkyl-phenyl, 2,4-bis(C1-C5)alkyl-phenyl, phenyl, fluorenyl, tetrahydrofluorenyl, indacenyl, hexahydroindacenyl, indenyl, dihydroindenyl, naphthyl, tetrahydronaphthyl, and phenanthrene. 40 Examples of aryl are substituted (C1-C 20 )Aryl, Substituted (C6-C 18 )aryl, 2,4-bis[(C 20 )alkyl]-phenyl, polyfluorophenyl, pentafluorophenyl, and fluoren-9-on-1-yl.
[0066] (C1~C 40 Examples of hydrocarbylenes include unsubstituted or substituted (C6-C 40 )Arylene, (C3-C 40 ) cycloalkylene, and (C1-C 40 ) Alkylene (e.g. (C1-C 20 ) alkylene). In some embodiments, the diradicals are on the same carbon atom (e.g., -CH2-), or on adjacent carbon atoms (i.e., 1,2-diradicals), or separated by one, two, or more than two intervening carbon atoms (e.g., 1,3-diradicals, 1,4-diradicals, etc., respectively). Some diradicals include α,ω-diradicals. α,ω-diradicals are diradicals with the greatest carbon backbone spacing between the radical carbons. (C2-C 20 Some examples of alkylene α,ω-diradicals include ethane-1,2-diyl (i.e., -CH2CH2-), propane-1,3-diyl (i.e., -CH2CH2CH2-), 2-methylpropane-1,3-diyl (i.e., -CH2CH(CH3)CH2-). (C6-C 50 ) Some examples of arylene α,ω-diradicals include phenyl-1,4-diyl, naphthalene-2,6-diyl, or naphthalene-3,7-diyl.
[0067] "(C1~C40 The term "alkylene" may be unsubstituted or may contain one or more R S means a saturated straight or branched diradical (i.e., the radicals are not on ring atoms) of 1 to 40 carbon atoms, substituted with 50 Examples of alkylene are unsubstituted (C1-C) alkylenes, including unsubstituted -CH2CH2-, -(CH2)3-, -(CH2)4-, -(CH2)5-, -(CH2)6-, -(CH2)7-, -(CH2)8-, -CH2C*HCH3, and -(CH2)4C*(H)CH3. 20 ) alkylene, where "C*" represents a carbon atom from which a hydrogen atom is removed to form a secondary or tertiary alkyl radical. 50 Examples of alkylene are substituted (C1-C 20 ) alkylene, -CF2-, -C(O)-, and -(CH2) 14 C(CH3)2(CH2)5- (i.e., 6,6-dimethyl-substituted normal-1,20-eicosylene). As mentioned above, the two R S Together (C1~C 18 ) alkylene, so that the substitution (C1-C 50 Examples of alkylene also include 1,2-bis(methylene)cyclopentane, 1,2-bis(methylene)cyclohexane, 2,3-bis(methylene)-7,7-dimethyl-bicyclo[2.2.1]heptane, and 2,3-bis(methylene)bicyclo[2.2.2]octane.
[0068] "(C3~C 40 The term "cycloalkylene" may be unsubstituted or may contain one or more R S "R" means a cyclic diradical (i.e., the radicals are on ring atoms) of 3 to 40 carbon atoms substituted by
[0069] The term "heteroatom" refers to an atom other than hydrogen or carbon. Examples of heteroatoms include O, S, S(O), S(O), Si(R C )2, P(R P ), N(R N ), -N=C(RC )2, -Ge(R C )2-, or -Si(R C )-, wherein each R C , each R N , and each R P is unsubstituted (C1 to C 18 ) hydrocarbyl or -H. The term "heterohydrocarbon" refers to a molecule or molecular skeleton in which one or more carbon atoms are replaced with a heteroatom. "(C1-C 40 The term "heterohydrocarbyl" means a heterohydrocarbon radical of 1 to 40 carbon atoms, and is used interchangeably with "(C1-C 40 The term "heterohydrocarbylene" means a heterohydrocarbon diradical of 1 to 40 carbon atoms, each heterohydrocarbon having one or more heteroatoms. The heterohydrocarbyl radical can be present on a carbon atom or a heteroatom, and the heterohydrocarbyl diradical can be present on (1) one or two carbon atoms, (2) one or two heteroatoms, or (3) one carbon atom and one heteroatom. Each (C1 to C 50 ) heterohydrocarbyl and (C1-C 50 ) Heterohydrocarbylene is unsubstituted or substituted (one or more R S The ring structure may be aromatic or non-aromatic, saturated or unsaturated, straight or branched chain, cyclic (including monocyclic and polycyclic, fused polycyclic and non-fused polycyclic) or acyclic.
[0070] (C1~C 40 ) Heterohydrocarbyl is unsubstituted or substituted (C1-C 40 )heteroalkyl, (C1-C 40 ) hydrocarbyl-O-, (C1-C 40 ) Hydrocarbyl-S-, (C1-C 40 ) hydrocarbyl-S(O)-, (C1-C 40 ) hydrocarbyl-S(O)2-, (C1-C 40 ) Hydrocarbyl-Si(R C )2-, (C1~C 40 )hydrocarbyl-N(R N )-, (C1~C 40 ) hydrocarbyl-P(RP )-, (C2~C 40 )heterocycloalkyl, (C2-C 19 )Heterocycloalkyl-(C1-C 20 ) alkylene, (C3-C 20 )Cycloalkyl-(C1-C 19 ) Heteroalkylene, (C2-C 19 )Heterocycloalkyl-(C1-C 20 ) Heteroalkylene, (C1-C 40 ) Heteroaryl, (C1-C 19 )Heteroaryl-(C1-C 20 ) Alkylene, (C6-C 20 )Aryl-(C1-C 19 ) heteroalkylene, or (C1-C 19 )Heteroaryl-(C1-C 20 ) heteroalkylene.
[0071] "(C4~C 40 The term "heteroaryl" refers to an unsubstituted or substituted heteroaryl group consisting of a total of 4 to 40 carbon atoms and 1 to 10 heteroatoms (one or more R S (C) means a monocyclic, bicyclic, or tricyclic heteroaromatic hydrocarbon radical, the monocyclic, bicyclic, or tricyclic radical containing, respectively, one, two, or three rings, the two or three rings being independently fused or non-fused, and at least one of the two or three rings being heteroaromatic. Other heteroaryl groups, such as, for example, generally (C x ~C y ) Heteroaryl, for example (C4-C 12 ) Heteroaryl) similarly has x to y carbon atoms (e.g., 4 to 12 carbon atoms) and is unsubstituted or substituted with one or more R SMonocyclic heteroaromatic hydrocarbon radicals are defined as being substituted by. Monocyclic heteroaromatic hydrocarbon radicals are 5- or 6-membered rings. Five-membered rings have 5 minus h carbon atoms, where h is the number of heteroatoms, which may be 1, 2, 3, or 4, and each heteroatom may be O, S, N, or P. Examples of 5-membered heteroaromatic hydrocarbon radicals include pyrrol-1-yl, pyrrol-2-yl, furan-3-yl, thiophen-2-yl, pyrazol-1-yl, isoxazol-2-yl, isothiazol-5-yl, imidazol-2-yl, oxazol-4-yl, thiazol-2-yl, 1,2,4-triazol-1-yl, 1,3,4-oxadiazol-2-yl, 1,3,4-thiadiazol-2-yl, tetrazol-1-yl, tetrazol-2-yl, and tetrazol-5-yl. The 6-membered ring has 6 minus h carbon atoms, where h is the number of heteroatoms, which may be 1 or 2, and the heteroatoms may be N or P. Examples of 6-membered heteroaromatic hydrocarbon radicals include pyridin-2-yl, pyrimidin-2-yl, and pyrazin-2-yl. The bicyclic heteroaromatic hydrocarbon radicals may be fused 5,6- or 6,6-ring systems. Examples of fused 5,6-ring bicyclic heteroaromatic hydrocarbon radicals are indol-1-yl and benzimidazol-1-yl. Examples of fused 6,6-ring bicyclic heteroaromatic hydrocarbon radicals are quinolin-2-yl and isoquinolin-1-yl. The tricyclic heteroaromatic hydrocarbon radicals may be fused 5,6,5-, 5,6,6-, 6,5,6-, or 6,6,6-ring systems. An example of a fused 5,6,5-ring system is 1,7-dihydropyrrolo[3,2-f]indol-1-yl. An example of a fused 5,6,6-ring system is 1H-benzo[f]indol-1-yl. An example of a fused 6,5,6-ring system is 9H-carbazol-9-yl. An example of a fused 6,6,6-ring system is acridine-9-yl.
[0072] The heteroalkyl group is any of (C1-C 50) carbon atoms or fewer and one or more of the heteroatoms. Similarly, heteroalkylene may be a saturated straight or branched chain diradical containing 1 to 50 carbon atoms and one or more of the heteroatoms. Heteroatoms as defined above include, but are not limited to, Si(R C )3, Ge(R C )3, Si(R C )2, Ge(R C )2, P(R P )2, P(R P ), N(R N )2, N(R N ), N, O, OR C , S, S.R. C , S(O), and S(O), each of the heteroalkyl and heteroalkylene groups may be unsubstituted or may include one or more R S is replaced by
[0073] Unsubstituted (C2~C 40 Examples of heterocycloalkyl are unsubstituted (C-C 20 )Heterocycloalkyl, unsubstituted (C2-C 10 ) heterocycloalkyl, aziridin-l-yl, oxetan-2-yl, tetrahydrofuran-3-yl, pyrrolidin-l-yl, tetrahydrothiophene-S,S-dioxid-2-yl, morpholin-4-yl, 1,4-dioxan-2-yl, hexahydroazepin-4-yl, 3-oxa-cyclooctyl, 5-thio-cyclononyl, and 2-aza-cyclodecyl.
[0074] In one or more embodiments, the catalyst system comprises a hydrocarbyl-modified methylaluminoxane and a metal-ligand complex. The hydrocarbyl-modified methylaluminoxane has less than 25 mole percent trihydrocarbylaluminum, based on the total moles of aluminum in the hydrocarbyl-modified methylaluminoxane. The trihydrocarbylaluminum is selected from the group consisting of AlR A1 R B1 R C1 (In the formula, R A1 , R B1 , and RC1 are independently 40 ) alkyl.
[0075] In embodiments, the hydrocarbyl-modified methylaluminoxane in the polymerization process has less than 20 mole percent and more than 5 mole percent trihydrocarbyl aluminum based on the total moles of aluminum in the hydrocarbyl-modified methylaluminoxane. In some embodiments, the hydrocarbyl-modified methylaluminoxane has less than 15 mole percent trihydrocarbyl aluminum based on the total moles of aluminum in the hydrocarbyl-modified methylaluminoxane. In one or more embodiments, the hydrocarbyl-modified methylaluminoxane has less than 10 mole percent trihydrocarbyl aluminum based on the total moles of aluminum in the hydrocarbyl-modified methylaluminoxane. In various embodiments, the hydrocarbyl-modified methylaluminoxane is a modified methylaluminoxane.
[0076] In some embodiments, the trihydrocarbylaluminum is AlR A1 R B1 R C1 (wherein R A1 , R B1 , and R C1 are independently 10 ) alkyl. In one or more embodiments, R A1 , R B1 , and R C1 is independently methyl, ethyl, propyl, 2-propyl, butyl, tert-butyl, or octyl. A1 , R B1 , and R C1 are the same. In another embodiment, R A1 , R B1 , and R C1 At least one of the R A1 , R B1 , and R C1 is different.
[0077] The term "hydrocarbyl-modified methylaluminoxane" refers to a methylaluminoxane (MMAO) structure that contains an amount of trihydrocarbylaluminum. The hydrocarbyl-modified methylaluminoxane contains a combination of a hydrocarbyl-modified methylaluminoxane matrix and trihydrocarbylaluminum. The total molar amount of aluminum in the hydrocarbyl-modified methylaluminoxane is composed of the aluminum contribution from the moles of aluminum from the hydrocarbyl-modified methylaluminoxane matrix and the moles of aluminum from the trihydrocarbylaluminum. The hydrocarbyl-modified methylaluminoxane contains more than 2.5 mole percent of trihydrocarbylaluminum based on the total moles of aluminum in the hydrocarbyl-modified methylaluminoxane. These additional hydrocarbyl substituents can affect the subsequent aluminoxane structure, resulting in differences in the distribution and size of aluminoxane clusters (Bryliakov, KP et al., Macromol. Chem. Phys. 2006, 207, 327-335). The additional hydrocarbyl substituents can also increase the solubility of the aluminoxane in hydrocarbon solvents such as, but not limited to, hexane, heptane, methylcyclohexane, and ISOPAR E™, as shown in U.S. Patent No. 5,777,143. Modified methylaluminoxane compositions are generally disclosed and can be prepared as described in U.S. Patent Nos. 5,066,631 and 5,728,855, both of which are incorporated herein by reference.
[0078] According to some embodiments, the catalyst system for producing the polyethylene composition comprises a metal-ligand complex according to formula (I): [ka]
[0079] In formula (I), M is a metal selected from titanium, zirconium, hafnium, scandium, yttrium, or the lanthanide series of the periodic table; n is 0, 1, or 2; when n is 1, X is a monodentate or bidentate ligand; when n is 2, each X is a monodentate ligand and is the same or different; the metal-ligand complex is overall charge neutral; and each Z is independently selected from -O-, -S-, -N(R N )- or -P(R P )-, and L is selected from (C1 to C 40 ) hydrocarbylene or (C1-C 40 ) heterohydrocarbylene, (C1-C 40 ) Hydrocarbylene has a moiety containing a linker skeleton of 1 to 10 carbon atoms connecting the two Z groups in formula (I) (to which L is attached), or 40 Heterohydrocarbylene has a moiety containing a linker skeleton of 1 to 10 atoms connecting the two Z groups in formula (I), and (C1 to C 40 Each of the 1 to 10 atoms of the 1 to 10 atom linker backbone of the heterohydrocarbylene is independently a carbon atom or a heteroatom, and each heteroatom is independently O, S, S(O), S(O), Si(R C )2, Ge(R C )2, P(R C ), or N(R C ), and independently, each R C is (C1~C 30 ) hydrocarbyl or (C1-C 30 ) heterohydrocarbyl, R 1 and R 8 are independently -H, (C1 to C 40 ) hydrocarbyl, (C1-C 40 ) heterohydrocarbyl, -Si(R C )3, -Ge(R C )3, -P(R P )2, -N(R N )2, -OR C , -SR C , -NO2, -CN, -CF3, R C S(O)-, RC S(O)2-, (R C )2C=N-, R C C(O)O-, R C OC(O)-, R C C(O)N(R N )-, (R N ) 2NC(O)-, halogen, and a radical having formula (II), formula (III), or formula (IV). [ka]
[0080] In formulas (II), (III), and (IV), R 31~35 , R 41~48 , or R 51~59 Each of the following is independently: 40 ) hydrocarbyl, (C1-C 40 ) heterohydrocarbyl, -Si(R C )3, -Ge(R C )3, -P(R P )2, -N(R N )2, N=CHR C , -OR C , -SR C , -NO2, -CN, -CF3, R C S(O)-, R C S(O)2-, (R C )2C=N-, R C C(O)O-, R C OC(O)-, R C C(O)N(R N )-, (R N ) 2NC(O)-, halogen, or -H, provided that R 1 or R 8 is a radical having formula (II), formula (III), or formula (IV).
[0081] In formula (I), R 2~4 , R 5~7 , and R 9~16 Each of the following is independently: 40 ) hydrocarbyl, (C1-C 40) heterohydrocarbyl, -Si(R C )3, -Ge(R C )3, -P(R P )2, -N(R N )2, -N=CHR C , -OR C , -SR C , -NO2, -CN, -CF3, R C S(O)-, R C S(O)2-, (R C )2C=N-, R C C(O)O-, R C OC(O)-, R C C(O)N(R N )-, (R C ) 2NC(O)-, halogen, and -H.
[0082] In some embodiments, the polyethylene composition is formed using a first metal-ligand complex according to formula (I) in a first reactor and a different metal-ligand complex according to formula (I) in a second reactor.
[0083] In one exemplary embodiment in which a dual loop reactor is used, the metal-ligand complex used in the first loop is zirconium, [[2,2′″-[[bis[1-methylethyl]germylene]bis(methyleneoxy-kO)]bis[3′,5,5″-tris(1,1-dimethylethyl)-5′-octyl[1,1′:3′,1″-terphenyl]-2′-olato-kO]](2-)]dimethyl-, prepared according to the procedures of WO 2018 / 183056, incorporated herein by reference, and having the chemical formula C 86 H 128 F2GeO4Zr and has the following structure (V): [ka]
[0084] In such an embodiment, the metal-ligand complex used in the second loop is zirconium, [[2,2'''-[1,3-propanediylbis(oxy-kO)]bis[3-[2,7-bis(1,1-dimethylethyl)-9H-carbazol-9-yl]]-5'-(dimethyloctylsilyl)-3'-methyl-5-(1,1,3,3-tetramethylbutyl)[1,1]-biphenyl]-2-olato-kO]](2-)]dimethyl, prepared according to the procedures of WO 2017 / 058981, incorporated herein by reference, and having the chemical formula C: 107 H 154 N2O4Si2Zr and has the following structure (VI): [ka]
[0085] Cocatalyst Component
[0086] The catalyst system comprising the metal-ligand complex of formula (I) may be catalytically activated by any technique known in the art for activating metal-based catalysts for olefin polymerization reactions. For example, the system comprising the metal-ligand complex of formula (I) may be catalytically activated by contacting the complex with or combining the complex with an activating cocatalyst.
[0087] In addition, the metal-ligand complexes according to formula (I) include both procatalyst forms which are neutral, and catalytic forms which can be positively charged by loss of a monoanionic ligand such as benzyl or phenyl. Suitable activating cocatalysts for use herein include oligomeric alumoxanes, modified alkylaluminoxanes or hydrocarbyl-modified methylaluminoxanes.
[0088] Suitable activating cocatalysts for use herein include alkylaluminum, polymeric or oligomeric alumoxanes (also known as aluminoxanes), neutral Lewis acids, and non-polymeric, non-coordinating, ion-forming compounds, including the use of such compounds under oxidizing conditions. A suitable activation technique is bulk electrolysis. Combinations of one or more of the foregoing activating cocatalysts and techniques are also contemplated. The term "alkylaluminum" refers to monoalkylaluminum dihydrides or dihalides, dialkylaluminum hydrides or halides, or trialkylaluminums. Examples of polymeric or oligomeric alumoxanes include methylalumoxane, triisobutylaluminum modified methylalumoxane, and isobutylalumoxane.
[0089] The Lewis acid activator (cocatalyst) may be any of the Lewis acid activators having one to three (C1-C 20 In one embodiment, the Group 13 metal compound includes a tri((C1-C) hydrocarbyl substituent. 20 )hydrocarbyl)substituted aluminum or tri((C1-C 20 In an embodiment, the Group 13 metal compound is a tri(hydrocarbyl)-substituted aluminum, tri((C1-C 20 )hydrocarbyl)-boron compounds, tri((C1-C 10 ) alkyl) aluminum, tri((C6-C 18 )aryl)boron compounds and their halogenated (including perhalogenated) derivatives. In further embodiments, the Group 13 metal compound is tris(fluoro-substituted phenyl)borane, tris(pentafluorophenyl)borane. In some embodiments, the activating cocatalyst is tris((C1-C 20 )hydrocarbyl)borate (e.g. trityl tetrafluoroborate) or tri((C 20 )hydrocarbyl)ammonium tetra((C1-C 20As used herein, the term "ammonium" refers to a (C1-C2) hydrocarbyl) borate (e.g., bis(octadecyl)methylammonium tetrakis(pentafluorophenyl)borate). 20 ) Hydrocarbyl) 4N + , ((C1~C 20 )hydrocarbyl)3N(H) + , ((C1~C 20 )hydrocarbyl)2N(H)2 + , (C1~C 20 ) HydrocarbylN(H)3 + , or N(H)4 + In the formula, each of (C1 to C 20 ) When two or more hydrocarbyls are present, they may be the same or different.
[0090] As a combination of neutral Lewis acid activators (cocatalysts), tri((C1-C4) alkyl)aluminum and tri((C6-C 18 )aryl)boron compounds, especially tris(pentafluorophenyl)borane. Embodiments include such neutral Lewis acid mixtures in combination with polymeric or oligomeric alumoxanes, and a single neutral Lewis acid, especially tris(pentafluorophenyl)borane in combination with polymeric or oligomeric alumoxanes. The molar ratio of (metal-ligand complex):(tris(pentafluorophenylborane):(alumoxane) [e.g., Group 4 metal-ligand complex):(tris(pentafluorophenylborane):(alumoxane)] is 1:1:1 to 1:10:30, in embodiments 1:1:1.5 to 1:5:10.
[0091] A catalyst system comprising the metal-ligand complex of formula (I) can be activated to form an active catalyst composition by combining one or more cocatalysts, such as cation-forming cocatalysts, strong Lewis acids, or combinations thereof. Suitable activating cocatalysts include polymeric or oligomeric aluminoxanes, particularly methylaluminoxane, and inert, compatible non-coordinating ion-forming compounds. Exemplary suitable cocatalysts include modified methyl aluminoxane (MMAO), bis(hydrogenated tallow alkyl)methyl tetrakis(pentafluorophenyl)borate (1 - ) amines, and combinations thereof.
[0092] In some embodiments, one or more of the aforementioned activating cocatalysts are used in combination with each other. Particularly preferred combinations are mixtures of tri((C1-C4)hydrocarbyl)aluminum, tri((C1-C4)hydrocarbyl)borane, or ammonium borate with an oligomeric or polymeric alumoxane compound. The ratio of the total number of moles of the one or more metal-ligand complexes of formula (I) to the total number of moles of the one or more activating cocatalysts is 1:10,000 to 100:1. In some embodiments, this ratio is at least 1:5000, in some embodiments at least 1:1000, and not more than 10:1, and in some embodiments, not more than 1:1. When an alumoxane is used alone as the activating cocatalyst, it is preferred that the number of moles of alumoxane used is at least 25 times the number of moles of the metal-ligand complexes of formula (I). When tris(pentafluorophenyl)borane is used alone as the activating cocatalyst, in some embodiments, the number of moles of tris(pentafluorophenyl)borane used relative to the total number of moles of one or more metal-ligand complexes of Formula (I) is from 0.5:1 to 10:1, from 1:1 to 6:1, or from 1:1 to 5:1. The remaining activating cocatalyst is generally used in a molar amount approximately equal to the total molar amount of one or more metal-ligand complexes of Formula (I).
[0093] film
[0094] In some embodiments, the disclosed embodiments relate to a film formed from any of the disclosed polyethylene compositions described herein. In some embodiments, the film may be a blown film or a cast film. In embodiments, the film may be an extrusion coated film. In embodiments, the film may be a blown machine direction oriented film or a cast film tenter frame oriented film. In some embodiments, the film may be a monolayer film. In some embodiments, the film may be a multilayer film. In some embodiments, the film may be a multilayer film. In some embodiments of a multilayer film comprising the disclosed polyethylene composition, the multilayer film may include the disclosed polyethylene-based composition in a surface layer and / or an inner layer. In embodiments, the disclosed polyethylene composition may be in a sealant layer of a multilayer film, where a multimodal polyethylene composition described herein is applied to at least one surface of the substrate layer to form a sealant layer associated with at least one surface of the substrate layer. The sealant layer may be applied to the substrate layer of a blown or cast film, for example, by a coextrusion process. In embodiments, the sealant layer may be applied directly to the substrate layer as an extrusion coating. The sealant layer may provide a heat sealable surface. As used herein, a heat-sealable surface is a surface that may allow a surface of a film to be heat sealed to another surface of the same film or to the surface of another film or substrate.
[0095] In one or more embodiments, the polyethylene compositions of the present disclosure may be blended with other polymers, such as other polyethylenes, or even other non-polyethylene polymers. For example, the polyethylene compositions of the present disclosure may be blended with conventional polyethylene compositions known to those of skill in the art, such as, but not limited to, LDPE, LLDPE, MDPE, and / or HDPE.
[0096] The amount of polyethylene composition used in the films of the present embodiments can depend on several factors, including, for example, whether the film is a monolayer or multilayer film, the other layers of the film if it is a multilayer film, the end use of the film, etc.
[0097] The film of the present invention may have a variety of thicknesses. The thickness of the film may depend on several factors, including, for example, whether the film is a monolayer film or a multilayer film, the other layers of the film if it is a multilayer film, the desired properties of the film, the end use of the film, the equipment available to manufacture the film, etc. In some embodiments, the film of the present disclosure has a thickness of up to 10 mils. For example, the film may have a thickness of 0.25 mils, 0.5 mils, 0.7 mils, 1.0 mils, 1.75 mils, or 2.0 mils, to an upper limit of 4.0 mils, 6.0 mils, 8.0 mils, or 10 mils. In embodiments, the film may have a thickness of 0.25 mils to 2.0 mils, 0.25 mils to 1.75 mils, 0.25 mils to 1.0 mils, 0.25 mils to 0.7 mils, 0.25 mils to 0.5 mils, 0.5 mils to 2.0 mils, 0.5 mils to 1.75 mils, 0.5 mils to 1.0 mils, 0.5 mils to 0.7 mils, 0.7 mils to 2.0 mils, 0.7 mils to 1.75 mils, 0.7 mils to 1.0 mils, 1.0 mils to 2.0 mils, 1.0 mils to 1.75 mils, 1.75 mils to 2.0 mils, or any combination.
[0098] In embodiments where the film comprises a multilayer film, the number of layers of the film can depend on several factors including, for example, the desired properties of the film, the desired thickness of the film, the content of other layers in the film, the end use of the film, the equipment available to manufacture the film, etc. Multilayer blown films can include up to 2, 3, 4, 5, 6, 7, 8, 9, 10, or 11 layers in various embodiments.
[0099] The polyethylene composition may be used in two or more layers of the film in some embodiments. Other layers in the multilayer film of the present disclosure may include polymers selected from the following in various embodiments: the polyethylene composition of the present disclosure, LLDPE, VLDPE (very low density polyethylene), MDPE, LDPE, HDPE, HMWHDPE (high molecular weight HDPE), propylene-based polymers, polyolefin plastomers (POP), polyolefin elastomers (POE), olefin block copolymers (OBC), ethylene vinyl acetate, ethylene acrylic acid, ethylene methacrylic acid, ethylene methyl acrylate, ethylene ethyl acrylate, ethylene butyl acrylate, isobutylene, maleic anhydride grafted polyolefins, ionomers of any of the foregoing, or combinations thereof. In some embodiments, the multilayer film of the present disclosure may include one or more tie layers known to those skilled in the art.
[0100] In additional embodiments of the films described herein, other layers may be adhered to the polyethylene film (possibly in addition to the barrier layer), for example, by a tie layer. Tie layers may be used to adhere layers of different materials. For example, a barrier layer comprising ethylene vinyl alcohol (EVOH) may be adhered to a polyethylene material by a tie layer (i.e., a tie layer comprising maleic anhydride grafted polyethylene). For example, the polyolefin film may further comprise other layers typically included in a multi-layer structure depending on the application, including, for example, other barrier layers, structural or strength layers, sealant layers, other tie layers, other polyethylene layers, polypropylene layers, etc. In additional embodiments, a printing layer may be included, which may be an ink layer applied to the film to show product details and other packaging information in various colors.
[0101] It should be understood that any of the foregoing layers may further comprise one or more additives as known to those skilled in the art, such as, for example, antioxidants, UV stabilizers, heat stabilizers, slip agents, antiblocking agents, pigments or colorants, processing aids, crosslinking catalysts, flame retardants, fillers, and blowing agents. In some embodiments, the polyethylene composition comprises up to 5 weight percent of such additional additives. All individual values and subranges from 0 to 5 weight percent are included and disclosed herein. For example, the total amount of additives in the polymer blend can be from a lower limit of 0, 0.5, 1, 1.5, 2, or 2.5 weight percent to an upper limit of 1.5, 2, 2.5, 3, 3.5, 4, 4.5, or 5 weight percent. In embodiments, the total amount of additives in the polymer blend is from 0 wt% to 5 wt%, 0 wt% to 4.5 wt%, 0 wt% to 4 wt%, 0 wt% to 3.5 wt%, 0 wt% to 3 wt%, 0 wt% to 2.5 wt%, 0 wt% to 2 wt%, 0 wt% to 1.5 wt%, 0 wt% to 1 wt%, 0 wt% to 0.5 wt%, 0.5 wt% to 5 wt%, 0.5 wt% to 4.5 wt%, 0.5 wt% to 4 wt%, 0. 5wt%~3.5wt%, 0.5wt%~3wt%, 0.5wt%~2.5wt%, 0.5wt%~2wt%, 0.5wt%~1.5wt%, 0.5wt%~1wt%, 1wt%~5wt%, 1wt Amount%~4.5% by weight, 1%~4% by weight, 1%~3.5% by weight, 1%~3% by weight, 1%~2.5% by weight, 1%~2% by weight, 1%~1.5% by weight, 1.5%~5% by weight, 1.5wt%~4.5wt%, 1.5wt%~4wt%, 1.5wt%~3.5wt%, 1.5wt%~3wt%, 1.5wt%~2.5wt%, 1.5wt%~2wt%, 2wt%~5wt% , 2% to 4.5% by weight, 2% to 4% by weight, 2% to 3.5% by weight, 2% to 3% by weight, 2% to 2.5% by weight, 2.5% to 5% by weight, 2.5% to 4.5% by weight, 2.5% by weight % to 4% by weight, 2.5% to 3.5% by weight, 2.5% to 3% by weight, 3% to 5% by weight, 3% to 4.5% by weight, 3% to 4% by weight, 3% to 3.5% by weight, 3.5% to 5% by weight, 3.5% to 4.5% by weight, 3.5% to 4% by weight, 4% to 5% by weight, 4% to 4.5% by weight, or 4.5% to 5% by weight, or any combination of these ranges.
[0102] The polyethylene composition of the present disclosure may be incorporated into multilayer films and articles that are primarily, if not substantially or entirely, composed of polyolefins, or more preferably polyethylene, to provide films and articles that are more easily recyclable, according to some embodiments. The polyethylene-based composition of the present disclosure is particularly advantageous for proving films in which the film is primarily formed from polyethylene. For example, monolayer or multilayer films in which the film primarily comprises polyethylene may have an improved recyclability profile in addition to other advantages that the use of such polymers may provide. In some embodiments, the film comprises 90% or more by weight of polyethylene, based on the total weight of the film. In other embodiments, the film comprises 91% or more by weight, 92% or more by weight, 93% or more by weight, 94% or more by weight, 95% or more by weight, 96% or more by weight, 97% or more by weight, 98% or more by weight, or 99% or more by weight of polyethylene, based on the total weight of the film.
[0103] In some embodiments, a film comprising a layer formed from the polyethylene-based composition of the present disclosure can be laminated to another film substrate. The substrate can include films comprising polyester, nylon, polypropylene, polyethylene, and combinations. For preferred recyclable substrates, biaxially oriented polyethylene (BOPE) substrates, machine direction oriented polyethylene (MDO) substrates, or coextruded polyethylene films can be included in the laminate structure.
[0104] In some embodiments, a film comprising a layer formed from the polyethylene composition of the present disclosure may be laminated to another film.
[0105] Films of the present disclosure, in some embodiments, can be corona treated and / or printed (eg, reverse printed or front printed) using techniques known to those of skill in the art.
[0106] In some embodiments, films of the present disclosure may be uniaxially (eg, machine direction) or biaxially oriented using techniques known to those of skill in the art.
[0107] In embodiments, monolayer blown films formed from the polyethylene compositions comprised herein and having a thickness of 2 mils may have a dart drop impact of at least 1000 grams, as measured according to ASTM D1709, Method A. In additional embodiments, monolayer blown films formed from the polyethylene compositions and having a thickness of 2 mils may have a dart drop impact of at least 1100 grams, at least 1200 grams, at least 1300 grams, at least 1400 grams, at least 1500 grams, at least 1600 grams, at least 1700 grams, at least 1800 grams, at least 1900 grams, or even at least 2000 grams, as measured according to ASTM D1709, Method A.
[0108] Goods
[0109]
[0023] Embodiments of the present disclosure also relate to articles, such as packaging, formed from or incorporating the polyethylene compositions of the present disclosure (or films incorporating the polyethylene compositions of the present disclosure). Such packaging can be formed from any of the polyethylene compositions of the present disclosure (or films incorporating the polyethylene-based compositions of the present disclosure) described herein.
[0110] Examples of such articles may include flexible packages, pouches, stand-alone pouches, and pre-made packages or pouches. In some embodiments, the multilayer films or laminates of the present disclosure may be used in food packaging. Examples of food products that may be included in such packaging include meat, cheese, cereal, nuts, juice, sauces, and the like. Such packaging may be formed using techniques known to those skilled in the art based on the teachings herein and based on the particular application of the packaging (e.g., type of food, amount of food, etc.).
[0111] Test Method
[0112] Unless otherwise indicated herein, the following analytical methods are used in describing the embodiments of the present disclosure.
[0113] Melt Index
[0114] The melt index I2 (or I2) and I 10 (or I10) were measured according to ASTM D-1238 (Method B) at 190°C and loads of 2.16 kg and 10 kg, respectively. The values are reported in g / 10 min. Fractions of the polymer samples were measured by collecting the product polymer from the reactor producing that particular fraction or portion of the polymer composition. For example, a first polyethylene fraction can be recovered from a reactor producing a lower density, higher molecular weight component of the polymer composition. Prior to the melt index measurement, the polymer solution is dried under vacuum.
[0115] density
[0116] Samples for density measurements were prepared according to ASTM D4703. Measurements were performed according to ASTM D792, Method B, within 1 hour of sample pressing.
[0117] ASTM D1709 Dirt Fall
[0118] The Film Dart Drop Test determines the energy that will break a plastic film under specified conditions of impact with a free falling dart. The test result is the energy, expressed as the weight of the impactor dropped from a specified height, that will result in 50% breakage of the specimens tested.
[0119] After the film is produced, it is conditioned for at least 40 hours at 23°C (±2°C) and 50% (±10) relative humidity according to ASTM standards. Standard test conditions are 23°C (±2°C) and 50% (±10) relative humidity according to ASTM standards.
[0120] Test results are reported by Method A, using a 1.5 inch diameter dart head and a drop height of 26 inches. The thickness of the sample is measured at the center of the sample, and the sample is then secured in a circular specimen holder with an inside diameter of 5 inches. The dart is loaded into the center, above, of the sample and released by either a pneumatic or electromagnetic mechanism.
[0121] The test is performed according to the "staircase" method. If the specimen breaks, the weight of the dart is reduced by a known fixed amount and a new specimen is tested. If the specimen does not break, a new specimen is tested with the weight of the dart increased by a known amount. After 20 specimens have been tested, the number of broken specimens is determined. If the number is 10, the test is completed. If the number is less than 10, the test is continued until 10 breaks are recorded. If the number is more than 10, the test is continued until the total number of unbroken specimens is 10. The dart drop strength is determined from these data according to ASTM D1709 and is expressed in grams as Type A dart drop impact. All analyzed specimens were 2 mils thick.
[0122] Instrumented Dart Impact
[0123] The instrumented dart impact method is measured on plastic film specimens according to ASTM D7192 using an Instron CEAST9350 impact tester. The test is performed using a 12.7 mm diameter tap with a hemispherical head, a 75 mm diameter clamp assembly with rubber faced grips. The instrument is equipped with an environmental chamber for testing at low or high temperatures. Typical specimen size is 125 mm x 125 mm. Standard test speed is 200 m / min. Film thickness is 2 mils.
[0124] Creep Zero Shear Viscosity Measurement Method
[0125] Zero shear viscosity is obtained via creep testing conducted on an AR-G2 stress-controlled rheometer (TA Instrument; New Castle, Del.) using 25 mm diameter parallel plates at 190° C. The rheometer oven is set to the test temperature for at least 30 minutes before zeroing the fixture. At the test temperature, a compression molded sample disk is inserted between the plates and allowed to equilibrate for 5 minutes. The upper plate is then lowered to 50 μm above the desired test gap (1.5 mm). Any excess material is trimmed away and the upper plate is lowered to the desired gap. Measurements are performed under a nitrogen purge with a flow rate of 5 L / min. The initial creep time is set to 2 hours.
[0126] To ensure that the steady-state shear rate is low enough in the Newtonian region, all of the samples are subjected to a constant low shear stress of 20 Pa. The resulting steady-state shear rate was 10 for the samples in this study. -3 ~10 -4 s -1 The steady state is determined by taking a linear regression on all the data in the last 10% time window of a plot of log(J(t)) versus log(t), where J(t) is the creep compliance and t is the creep time. If the slope of the linear regression is greater than 0.97, the steady state is considered to have been reached and the creep test is then stopped. In this study, in all cases, the slope meets the criterion within 2 hours. The steady state shear rate is determined from the slope of the linear regression of all the data points in the last 10% time window of a plot of ε versus t, where ε is the strain. The zero shear viscosity is determined from the ratio of the applied stress to the steady state shear rate.
[0127] To determine if the specimen has degraded during the creep test, perform small amplitude oscillatory shear tests before and after the creep test on the same specimen at 0.1 to 100 rad / s. Compare the complex viscosity values of the two tests. If the difference in viscosity value at 0.1 rad / s is greater than 5%, consider the specimen to have degraded during the creep test and discard the results.
[0128] Gel Permeation Chromatography (GPC)
[0129] The chromatography system consisted of a PolymerChar (Valencia, Spain) GPC-IR high temperature GPC chromatograph equipped with an internal IR5 infrared detector (IR5). The autosampler oven compartment was set at 160°C and the column compartment was set at 150°C. The columns used were four Agilent "Mixed A" 30 cm 20 micron linear mixed bed columns and a 20 um precolumn. The chromatography solvent used was 1,2,4-trichlorobenzene containing 200 ppm butylated hydroxytoluene (BHT). The solvent source was nitrogen sparged. The injection volume employed was 200 microliters and the flow rate was 1.0 milliliters / min.
[0130] Calibration of the GPC column set was performed with 21 narrow molecular weight distribution polystyrene standards with molecular weights ranging from 580 to 8,400,000, arranged in six "cocktail" mixtures with at least 10-fold spacing between individual molecular weights. Standards were purchased from Agilent Technologies. Polystyrene standards were prepared at 0.025 grams in 50 milliliters of solvent for molecular weights equal to or greater than 1,000,000, and at 0.05 grams in 50 milliliters of solvent for molecular weights less than 1,000,000. The polystyrene standards were dissolved at 80°C for 30 minutes with gentle agitation. The peak molecular weights of the polystyrene standards were converted to polyethylene molecular weights using Equation 1 (as described in Williams and Ward, J. Polym. Sci., Polym. Let., 6, 621 (1968)):
number
[0131] A fifth order polynomial was used to fit each of the polyethylene equivalent calibration points, with a small adjustment (approximately 0.375 to 0.445) made to A to correct for column resolution and band broadening effects for a linear homopolymer polyethylene standard obtained at 120,000 Mw.
[0132] Total plate counts of the GPC column set were performed using decane (prepared at 0.04 g in 50 milliliters of TCB and dissolved for 20 minutes with gentle agitation). Plate counts (Equation 2) and symmetry (Equation 3) were measured with a 200 microliter injection according to the following equations:
number
number
[0133] Samples were prepared in a semi-automated fashion using PolymerChar's "Instrument Control" software to target sample weights of 2 mg / ml and add solvent (containing 200 ppm BHT) via a PolymerChar high temperature autosampler to pre-nitrogen sparged capped vials with septa. Samples were dissolved at 160° C. for 2 hours under "slow" shaking.
[0134] Mn (GPC) , Mw (GPC) , and Mz (GPC) The calculations were based on GPC results using the internal IR5 detector (measurement channel) of a PolymerChar GPC-IR chromatograph according to Equations 4-6 using PolymerChar GPCOne™ software, baseline-subtracted IR chromatograms at each equally spaced data collection point (i), and polyethylene equivalent molecular weights obtained from a narrow standard calibration curve for point (i) of Equation 1.
number
number
number
[0135] To monitor deviations over time, a flow rate marker (decane) was introduced into each sample via a micropump controlled by a PolymerChar GPC-IR system. This flow rate marker (FM) was used to linearly correct the pump flow rate (flow rate (apparent)) of each sample by RV matching the respective decane peak in the sample (RV (FM sample)) with that of the decane peak in the narrow standard calibration (RV (FM calibrated)). Any change in time of the decane marker peak is then assumed to be related to a linear shift in flow rate (flow rate (effective)) throughout the run. To facilitate the highest accuracy of the RV measurement of the flow rate marker peak, a least squares fitting routine is used to fit the peaks of the flow rate marker concentration chromatogram to a quadratic equation. The first derivative of the quadratic equation is then used to solve for the true peak position. After calibrating the system based on the flow rate marker peak, the effective flow rate (relative to the narrow standard calibration) is calculated as per Equation 7. Processing of the flow rate marker peaks was performed via PolymerChar GPCOne™ software. An acceptable flow correction is such that the effective flow rate should be within ±0.5% of the apparent flow rate.
number
[0136] Improved Method for Comonomer Content Analysis (iCCD)
[0137] An improved comonomer content analysis method (iCCD) was developed in 2015 (Cong and Parrott et al., WO 2017 / 040127(A1)). iCCD testing was performed using a Crystallization Elution Fractionation (CEF) instrument (PolymerChar, Spain) equipped with an IR-5 detector (PolymerChar, Spain) and a two-angle light scattering detector model 2040 (Precision Detectors, now Agilent Technologies). A 5 cm or 10 cm (length) x ¼ inch (ID) guard column packed with 20–27 micron glass (MoSCi Corporation, USA) on stainless steel was placed immediately before the IR-5 detector in the detector oven. Ortho-dichlorobenzene (ODCB, 99% anhydrous grade or technical grade) was used. Silica gel 40 (particle size 0.2-0.5 mm, catalog number 10181-3) was obtained from EMD Chemicals (which may be used to dry the ODCB solvent prior). The CEF instrument is equipped with an autosampler with N2 purging capability. ODCB is sparged with dry nitrogen (N2) for 1 h prior to use. Sample preparation was performed at 4 mg / mL (unless otherwise specified) using the autosampler with shaking at 160 °C for 1 h. Injection volume was 300 μL. The temperature profile for the iCCD was crystallization from 105 °C to 30 °C at 3 °C / min, thermal equilibration at 30 °C for 2 min (including setting the soluble fraction elution time to 2 min), and elution from 30 °C to 140 °C at 3 °C / min. The flow rate during crystallization is 0.0 mL / min. The flow rate during elution is 0.50 mL / min. Data is collected at 1 data point / sec.
[0138] The iCCD column was packed with gold-coated nickel particles (Bright 7GNM8-NiS, Nippon Chemical Industrial Co.) in a 15 cm (length) x ¼ inch (ID) stainless steel tube. Column packing and conditioning was performed with a slurry method according to references (Cong, R.; Parrott, A.; Hollis, C.; Cheatham, M. International Publication WO 2017040127(A1)). The final pressure using TCB slurry packing was 150 bar.
[0139] Column temperature calibration was performed using the reference material linear homopolymer polyethylene in ODCB (comonomer content zero, melt index (I2) 1.0, polydispersity M w / M n Conventional gel permeation chromatography was performed using a mixture of 1.0 mg / mL of glycerol (~2.6) and eicosane (2 mg / mL). The iCCD temperature calibration consisted of four steps: (1) calculating the delay volume, defined as the temperature offset between the measured peak elution temperatures of eicosane minus 30.00°C, and (2) subtracting the temperature offset of the elution temperature from the iCCD raw temperature data. Note that this temperature offset is a function of the experimental conditions, such as elution temperature, elution flow rate, etc. (3) creating a linear calibration line converting elution temperatures over the range of 30.00°C to 140.00°C such that the linear homopolymer polyethylene reference material has a peak temperature at 101.0°C and eicosane has a peak temperature of 30.0°C; (4) linearly extrapolating elution temperatures below 30.0°C for the soluble fraction measured isothermally at 30°C by using an elution heating rate of 3°C / min according to reference (Cerk and Cong et al., U.S. Patent No. 9,688,795).
[0140] Comonomer content versus iCCD elution temperature was constructed using 12 reference materials (ethylene homopolymers and ethylene-octene random copolymers made with a single-site metallocene catalyst, with ethylene equivalent weight average molecular weights ranging from 35,000 to 128,000). All of these reference materials were analyzed in the same manner as previously specified at 4 mg / mL. The reported elution peak temperatures were linearly fitted to the linear equation y=-6.3515x.+101.00, where y represents the iCCD elution temperature, x represents the octene mole %, and R 2 was 0.978.
[0141] The molecular weights of the polymers and polymer fractions were determined directly from the LS detector (at a 90 degree angle) and the concentration detector (IR-5) according to the Rayleigh-Gans-Debys approximation (Striegel and Yau, "Modern Size Exclusion Liquid Chromatogram", Page 242 and Page 263) by assuming a form factor of 1 and all virial coefficients of zero. An integration window was set to integrate all chromatograms with elution temperatures ranging from 23.0 to 120 °C (temperature calibration specified above).
[0142] Calculation of molecular weight (Mw) from iCCD involves four steps:
[0143] (1) Step of measuring the inter-detector offset. The offset is defined as the geometric volume offset between the LS detector and the concentration detector. It is calculated as the difference in the elution volume (mL) of the polymer peak between the concentration detector and the LS chromatogram. This is converted to a temperature offset by using the elution heat rate and the elution flow rate. A linear high density polyethylene (comonomer content zero, melt index (I2) of 1.0, polydispersity M w / M nThe flow rate is approximately 2.6 for conventional gel permeation chromatography. The same experimental conditions as for the conventional iCCD method above are used, except for the following parameters: crystallization from 140°C to 137°C at 10°C / min, thermal equilibration at 137°C for 1 min for soluble fraction elution time, soluble fraction (SF) time of 7 min, elution from 137°C to 142°C at 3°C / min. The flow rate during crystallization is 0.0 mL / min. The flow rate during elution is 0.80 mL / min. The sample concentration is 1.0 mg / mL.
[0144] (2) Shift each LS data point in the LS chromatogram to correct for inter-detector offset before integration.
[0145] (3) The baseline-subtracted LS and concentration chromatograms are integrated over the elution temperature range of step (1). The MW detector constant is calculated using HDPE samples of known MW in the range of 100,000-140,000 MW and the area ratio of the LS and concentration integrated signals.
[0146] (4) The Mw of the polymer was calculated by using the ratio of the integrated light scattering detector (at a 90 degree angle) to the concentration detector and using the MW detector constant.
[0147] The half-width calculation is defined as the temperature difference between the forward and rearward temperatures at half the maximum peak height, where the forward temperature at half the maximum peak is searched forward from 35.0°C and the rearward temperature at half the maximum peak is searched backward from 119.0°C.
[0148] Zero-shear viscosity ratio (ZSVR)
[0149] ZSVR is defined as the ratio of the zero shear viscosity (ZSV) of a branched polyethylene material to the ZSV of a linear polyethylene material at equivalent weight average molecular weight (Mw-gpc) according to Equations (EQ) 8 and 9 below.
number
number
[0150] ZSV values were obtained from creep tests at 190°C by the method described above. Mw-gpc values were determined by the conventional GPC method (Equation 5 in the description of the conventional GPC method). A correlation between the ZSV of a linear polyethylene and its Mw-gpc was established based on a series of linear polyethylene reference materials. A description of the ZSV-Mw relationship can be found in the ANTEC Abstract: Karjala, Teresa P., Sammler, Robert L., Mangnus, Marc A., Hazlitt, Lonnie G., Johnson, Mark S., Hagen, Charles M. Jr., Huang, Joe WL, Reichek, Kenneth N., "Detection of low levels of long-chain branching in polyolefins", Annual Technical Conference-Society of Plastics Engineers (2008), 66th 887-891.
[0151] Dynamic Rheological Analysis
[0152] To characterize the rheological behavior of substantially linear ethylene polymers, S Lai and GW Knight (ANTEC'93 Proceedings, Insite™ Technology Polyolefins (ITP)—New Rules in the Structure / Rheology Relationship of Ethylene &-Olefin Copolymers, New Orleans, La., May 1993) introduced a new rheological measurement, the Dow Rheology Index (DRI), which represents the "normalized relaxation time as a result of long chain branching" of a polymer. S. Lai et al; (ANTEC'94, Dow Rheology Index (DRI) for Insite™ Technology Polyolefins (ITP): Unique structure-Processing Relationships, pp. 1814-1815) defined the DRI as the extent to which the rheology of ethylene-octene copolymers known as ITPs (Dow's Insite Technology Polyolefins), which have long chain branching incorporated into the polymer backbone, deviates from the rheology of conventional linear homogeneous polyolefins reported to have no long chain branching (LCB) by the following normalized equation:
number
number
[0153] Dynamic rheology measurements are performed in a dynamic rheometer (e.g., ARES rheometer from TA Instruments) with 25 mm diameter parallel plates in dynamic mode under an inert atmosphere according to ASTM D4440. For all experiments, the rheometer is thermally stabilized at 190°C for at least 30 minutes before inserting the compression molded sample, properly stabilized (with antioxidant additives), onto the parallel plates. The plates are then closed with a positive normal force registered on the meter to ensure good contact. After about 5 minutes at 190°C, the plates are lightly compressed and excess polymer around the plates is trimmed. An additional 10 minutes are allowed for the thermal stability and normal forces to return to zero. Thus, all measurements are performed after the samples are equilibrated at 190°C for about 15 minutes and performed under a full nitrogen atmosphere.
[0154] Two strain sweep (SS) experiments are first performed at 190 °C to determine the linear viscoelastic strain that gives rise to a torque signal that is greater than 10% of the lower scale of the transducer over the full frequency range (e.g., 0.01-100 rad / s). The first SS experiment is performed at a low applied frequency of 0.1 rad / s. This test is used to determine the sensitivity of the torque at low frequencies. The second SS experiment is performed at a high applied frequency of 100 rad / s. This is to ensure that the selected applied strain is well within the linear viscoelastic region of the polymer so that the oscillatory rheological measurements do not induce structural changes to the polymer during testing. Additionally, a time sweep (TS) experiment is performed at a low applied frequency of 0.1 rad / s at the selected strain (determined by the SS experiment) to check the stability of the sample during testing.
[0155] The storage modulus (or elastic modulus), loss modulus (or viscous modulus) (G″), complex modulus (G*), complex viscosity (η*), and tan δ (ratio of loss modulus to storage modulus, G′VG′) were obtained as a function of frequency (ω) at a given temperature (e.g., 190° C.). EXAMPLES
[0156] Example 1: Preparation of polyethylene compositions 1 and 2
[0157] Polyethylene compositions 1 and 2 described according to one or more embodiments of the detailed description were prepared using a catalyst and reactor by the method described below.
[0158] All raw materials (monomers and comonomers) and process solvents (high purity narrow boiling range isoparaffinic solvent, Isopar-E) were purified with molecular sieves prior to introduction into the reaction environment. Hydrogen was supplied under pressure as a high purity grade with no further purification. The reactor monomer feed stream was pressurized above the reaction pressure via a mechanical compressor. Solvent and comonomer feeds were pressurized to pressures above the reaction pressure by pumps. Individual catalyst components were manually batch diluted with purified solvent and pressurized to the reaction pressure above. All reaction feed streams were metered with mass flow meters and independently controlled with a computerized automated valve control system.
[0159] Two reactor systems were used in a series configuration. The first reactor was a continuous solution polymerization reactor consisting of a liquid-filled, non-adiabatic, isothermal, circulating, loop reactor mimicking a continuous stirred tank reactor (CSTR) with heat removal. Independent control of all fresh solvent, monomer, comonomer, hydrogen, and catalyst component feeds was possible. All fresh feed streams (solvent, monomer, comonomer, and hydrogen) to the first reactor were temperature controlled to maintain a single solution phase by passing the feed streams through heat exchangers. All fresh feed to the first polymerization reactor was injected into the reactor at two locations, with reactor volumes approximately equal between each injection location. The fresh feed was controlled with each injector receiving half of the total fresh feed mass flow rate. The catalyst components were injected into the polymerization reactor separately from the fresh feed. The feed of the main catalyst components was computer controlled to maintain the monomer conversion of the reactor at a specific value. The cocatalyst components were fed based on a molar ratio to the main catalyst component or to target reactor concentrations. Immediately after the injection point of each first reactor feed, the feed stream was mixed with the contents of the circulation polymerization reactor using a static mixing element. The contents of the first reactor were continuously circulated through a heat exchanger, which served to remove most of the heat of reaction, at a coolant side temperature, which served to maintain an isothermal reaction environment at a specific temperature. Circulation around the first reactor loop was provided by a pump.
[0160] The second reactor was a continuous solution polymerization reactor consisting of a liquid-filled adiabatic continuous stirred tank reactor (CSTR). Independent control of all fresh solvent, monomer, comonomer, hydrogen, and catalyst component feeds was possible. All fresh feed streams (solvent, monomer, comonomer, and hydrogen) to the second reactor were temperature controlled to maintain a single solution phase by passing the feed streams through heat exchangers. All fresh feeds to the second polymerization reactor were injected into the reactor at one location. Catalyst components were injected into the second polymerization reactor separately from the fresh feeds. The feed of the main catalyst component was computer controlled to maintain the monomer conversion of the reactor at a specific value. The cocatalyst component was fed based on a specific molar ratio to the main catalyst component or to achieve a specific concentration of the cocatalyst component relative to the fresh feed stream to the reactor. Mixing in the second reactor was provided by an agitator. The effluent from the first polymerization reactor (containing solvent, monomer, comonomer, hydrogen, catalyst components, and polymer) exited the first reactor loop and was added to the second reactor separately from the fresh feed and separately from the catalyst feed components.
[0161] The second reactor effluent entered a zone where the effluent was deactivated by addition and reaction with a suitable reagent (water). Antioxidant addition can also be done at this same addition point. Following catalyst deactivation and additive addition, the reactor effluent entered a devolatilization system where polymer was removed from the non-polymer stream. The isolated polymer melt was pelletized and collected. The non-polymer stream passed through various equipment that separated most of the ethylene removed from the system. Most of the solvent and unreacted comonomer were recycled to the reactor after passing through a purification system. Small amounts of solvent and comonomer were purged from the process.
[0162] The reactor stream feed data flows corresponding to the values in Table 1 used to generate the examples are set forth graphically in Figure 2. The data are displayed to allow for the complexity of the solvent recycle system and to allow the reaction system to be more easily treated as a once-through flow diagram. Table 2 shows the catalyst components referenced in Table 1. [Table 1] [Table 2] * Modified with n-octyl substituents such that the methyl:n-octyl ratio is approximately 6:1 and contains 10-20% trialkylaluminum species
[0163] Example 2: Comparative polyethylene compositions A to L
[0164] Comparative compositions A-C were prepared by the methods described herein below. Comparative compositions D-F are bimodal polyethylene compositions generally prepared using the catalyst system and process provided for preparing the first composition of the invention in PCT Publication No. 2015 / 200743. Comparative compositions G-J are commercially available polyethylene compositions. Table 3 shows the commercially available polyethylene compositions of comparative compositions G-J. [Table 3]
[0165] The preparation of Comparative Compositions A-C is described as follows: All raw materials (monomers and comonomers) as well as process solvents (high purity narrow boiling range isoparaffinic solvent, Isopar-E) are purified with molecular sieves prior to introduction into the reaction environment. Hydrogen is supplied under pressure as a high purity grade and is not further purified. The monomer feed stream to the reactor is pressurized to a pressure above the reaction pressure by a mechanical compressor. The solvent and comonomer feeds are pressurized to a pressure above the reaction pressure by pumps. The individual catalyst components are manually batch diluted with purified solvent and pressurized above the reaction pressure. All reaction feed streams are metered with mass flow meters and independently controlled by computer automated valve control systems.
[0166] Two reactor systems are used in a series configuration. Each continuous solution polymerization reactor consists of a liquid-filled, non-adiabatic, isothermal circulating loop reactor replicating a continuously stirred tank reactor (CSTR) with heat removal. Independent control of all fresh solvent, monomer, comonomer, hydrogen, and catalyst component feeds is possible. All fresh feed streams to each reactor (solvent, monomer, comonomer, and hydrogen) are temperature controlled to maintain a single solution phase by passing the feed streams through heat exchangers. All fresh feed to each polymerization reactor is injected into the reactor at two points with approximately equal reactor volume between each injection point. Fresh feed is controlled with each injector receiving half of the total fresh feed mass flow rate. Catalyst components are injected into the polymerization reactors through injection stingers. The main catalyst component feeds are computer controlled to maintain the monomer conversion of each reactor at a specific target value. The cocatalyst components are fed based on a specific calculated molar ratio to the main catalyst component. Immediately after the injection point of each reactor feed, the feed stream is mixed with the contents of a circulation polymerization reactor with static mixing elements. The contents of each reactor are passed through a heat exchanger that serves to remove most of the heat of reaction, and are continuously circulated with the coolant side temperature serving to maintain an isothermal reaction environment at a specific temperature. Circulation around each reactor loop is provided by a pump.
[0167] In a dual reactor in series configuration, the effluent from the first polymerization reactor (containing solvent, monomer, comonomer, hydrogen, catalyst components, and polymer) exits the first reactor loop and is added to the second reactor loop.
[0168] The second reactor effluent enters a zone where a suitable reagent (water) is added to deactivate the effluent by reacting with it. At the outlet of this same reactor, other additives are added for polymer stabilization (typical antioxidants suitable for stabilization during extrusion and film fabrication, such as octadecyl 3,5-di-Tert-butyl-4-hydroxyhydrocinnamate, tetrakis(methylene(3,5-di-Tert-butyl-4-hydroxyhydrocinnamate))methane, and tris(2,4-di-Tert-butyl-phenyl)phosphite).
[0169] Following catalyst deactivation and additive addition, the reactor effluent enters a devolatilization system where polymer is removed from the non-polymer stream. The isolated polymer melt is pelletized and recovered. The non-polymer stream passes through various equipment that separates most of the ethylene, which is removed from the system. Most of the solvent and unreacted comonomer are recycled to the reactor after passing through a purification system. Small amounts of solvent and comonomer are purged from the process.
[0170] The reactor stream feed data flows correspond to the values in Table 4. The data is displayed to allow for the complexity of the solvent recycle system and to make the reaction system easier to treat as a once-through flow diagram. Table 6 shows the catalysts and cocatalysts shown in Table 4. [Table 4]
[0171] Comparative polyethylene compositions KL were prepared utilizing the catalysts and reactors according to the methods described below.
[0172] All raw materials (monomers and comonomers) and process solvents (high purity narrow boiling range isoparaffinic solvent, Isopar-E) were purified with molecular sieves prior to introduction into the reaction environment. Hydrogen was supplied under pressure as a high purity grade with no further purification. The reactor monomer feed stream was pressurized above the reaction pressure via a mechanical compressor. Solvent and comonomer feeds were pressurized to pressures above the reaction pressure by pumps. Individual catalyst components were manually batch diluted with purified solvent and pressurized to the reaction pressure above. All reaction feed streams were metered with mass flow meters and independently controlled with a computerized automated valve control system.
[0173] Two reactor systems were used in a series configuration. Each continuous solution polymerization reactor consisted of a liquid-filled, non-adiabatic, isothermal circulating loop reactor replicating a continuous stirred tank reactor (CSTR) with heat removal. Independent control of all fresh solvent, monomer, comonomer, hydrogen, and catalyst component feeds was possible. All fresh feed streams to each reactor (solvent, monomer, comonomer, and hydrogen) were temperature controlled to maintain a single solution phase by passing the feed streams through heat exchangers. The total fresh feed to each polymerization reactor was injected into the reactor at two locations, with reactor volumes approximately equal between each injection location. Fresh feed was controlled with each injector receiving half of the total fresh feed mass flow rate. Catalyst components were injected into the polymerization reactors by injection stingers. The feed of the primary catalyst components was computer controlled to maintain the monomer conversion of each reactor at a specific target. The cocatalyst components were fed to the primary catalyst components based on a specific calculated molar ratio. Immediately after each reactor feed injection point, the feed stream was mixed with the contents of the circulation polymerization reactor using a static mixing element. The contents of each reactor were continuously circulated to a heat exchanger, which served to remove the majority of the heat of reaction, with the coolant side serving to maintain an isothermal reaction environment at a specific temperature. Circulation around each reactor loop was provided by a pump.
[0174] In the dual reactor in series configuration, the effluent from the first polymerization reactor (containing solvent, monomer, comonomer, hydrogen, catalyst components, and polymer) exited the first reactor loop and was added to the second reactor loop.
[0175] The second reactor effluent entered a zone where it was inactivated by addition and reaction with a suitable reagent (water).At this same reactor exit location, other additives were added to stabilize the polymer (typical antioxidants suitable for stabilization during extrusion and film fabrication, such as octadecyl 3,5-di-Tert-butyl-4-hydroxyhydrocinnamate, tetrakis(methylene(3,5-di-Tert-butyl-4-hydroxyhydrocinnamate))methane, and tris(2,4-di-Tert-butyl-phenyl)phosphite).
[0176] Following catalyst deactivation and additive addition, the reactor effluent entered a devolatilization system where polymer was removed from the non-polymer stream. The isolated polymer melt was pelletized and collected. The non-polymer stream passed through various equipment that separated most of the ethylene, which was removed from the system. Most of the solvent and unreacted comonomer were recycled to the reactor after passing through a purification system. Small amounts of solvent and comonomer were purged from the process.
[0177] Reactor flow feed data is shown in Table 5. The data is presented to allow for the complexity of the solvent recycle system and to allow the reaction system to be more easily treated as a once-through flow diagram. Table 6 shows the catalyst components referenced in Table 5. [Table 5] [Table 6]
[0178] Example 3: Analysis of polyethylene compositions 1-2 and comparative polyethylene compositions A-L
[0179] Polyethylene Compositions 1-2 of Example 1 and Comparative Polyethylene Compositions A-L of Example 2 were analyzed by iCCD. Additional data generated from iCCD testing of all samples is provided in Tables 7 and 8. Specifically, Tables 7 and 8 include an analysis of the iCCD data including areas (45-90°C and 90-120°C) of the first and second polyethylene fractions, respectively. Additional data for each example composition is also provided including overall density, dart strength (Method A), melt index, and weight average molecular weight in the second PE fraction. These properties are based on monolayer blown films comprised entirely of each polyethylene sample.
[0180] Polyethylene samples were used to form 2 mil blown films to perform dart testing and other tests based on the films formed. Specifically, monolayer blown films were produced by an Egan Davis Standard extruder equipped with a 3.5 inch ID half grooved barrel, a 30 / 1 L / D ratio, a barrier screw, and an Alpine air ring. The extrusion line has an 8 inch die with internal bubble cooling. The extrusion line also has a film thickness gauge scanner. The film production conditions were: film thickness was maintained at 2 mils (0.001 inch or 0.0254 mm), blow up ratio (BUR) was 2.5, die gap was 70 mils, and frost line height (FLH) was 37 inches. Output rate was constant at 260 lbs / hr. [Table 7] [Table 8]
[0181] As shown in Tables 7 and 8, the results show that, for all of the comparative samples A to L, the ratio of the area of the first polyethylene fraction to the area of the second polyethylene fraction was 2.0 to 4.0, and the average porosity was at least 0.924 g / cm. 3 This indicates that the overall density of the darts did not provide equivalent dart strength.
[0182] It will be apparent that modifications and variations are possible without departing from the scope of the present disclosure, as defined in the appended claims. More specifically, although certain aspects of the present disclosure are identified herein as preferred, exemplary, or particularly advantageous, it is contemplated that the present disclosure is not necessarily limited to those aspects.
[0183] It should be noted that one or more of the claims that follow utilize the term "herein" as a transitional phrase. It should be noted that for purposes of defining the invention, this term is introduced into the claims as an open-ended transitional phrase used to introduce a recitation of a series of features of a structure, and is to be interpreted in a similar manner to the more commonly used open-ended preamble term "comprising."
Claims
1. 1. A polyethylene composition comprising: a first polyethylene fraction area defined by the area within a temperature range of 45° C. to 90° C. of an elution profile by improved comonomer composition distribution (iCCD) analysis; a first peak in the temperature range of 45° C. to 90° C. of the elution profile; a second polyethylene fraction area defined by the area of said elution profile within a temperature range of 90° C. to 120° C.; and a second peak in the elution profile within the temperature range of 90° C. to 120° C.; a minimum in the temperature range of 80°C to 95°C of the elution profile by iCCD analysis; The polyethylene composition has a viscosity of 0.924 g / cm 3 ~0.936g / cm 3 and a melt index (I 2 ), wherein a ratio of the first polyethylene fraction area to the second polyethylene fraction area is from 2.0 to 4.0, and wherein the first polyethylene fraction area constitutes from 60% to 80% of a total area of the elution profile.
2. 2. The polyethylene composition according to claim 1, wherein the polyethylene composition has a molecular weight distribution, expressed as the ratio of weight average molecular weight to number average molecular weight (Mw / Mn), in the range of 2.5 to 8.
0.
3. 3. The polyethylene composition according to claim 1 or 2, wherein said first peak in the temperature range of 45°C to 90°C of said elution profile is a first single peak, and said first polyethylene fraction area is the area in the elution profile under said first single peak of the first polyethylene fraction from 45°C to 90°C.
4. 4. The polyethylene composition according to any one of claims 1 to 3, wherein said second peak in the temperature range of 90°C to 120°C of said elution profile is a second single peak, and said second polyethylene fraction area is the area in the elution profile under said second single peak of the second polyethylene fraction from 90°C to 120°C.
5. 5. The polyethylene composition according to any one of claims 1 to 4, wherein the second polyethylene fraction area constitutes between 10% and 50% of the total area of the elution profile.
6. The polyethylene composition according to any one of claims 1 to 5, wherein the polyethylene composition has a zero shear viscosity ratio of less than 3.
0.
7. The polyethylene composition according to any one of claims 1 to 6, wherein the width at 50 percent peak height of the single peak of the second polyethylene fraction is less than 10.0°C.
8. 8. The polyethylene composition according to any one of the preceding claims, wherein the difference between said single peak of said second polyethylene fraction and said single peak of said first polyethylene fraction is at least 10°C.
9. The first polyethylene fraction has a melt index (I 2 The polyethylene composition according to any one of claims 1 to 8, wherein
10. 10. The polyethylene composition according to any one of the preceding claims, wherein the second polyethylene fraction has a molecular weight of less than 100,000 as measured by improved comonomer composition distribution (iCCD) analysis.
11. A film comprising the polyethylene composition according to any one of claims 1 to 10.
12. The film of claim 11 , wherein the film is a multilayer film.
13. The film of claim 11 , wherein the film is a monolayer film.
14. 12. The film of claim 11, wherein a monolayer blown film formed from the polyethylene composition and having a thickness of 2 mils has a dart drop impact of at least 1000 grams as measured according to ASTM D1709, Method A.
Citation Information
Patent Citations
Multilayer films having at least three layers and methods of producing the same
WO2021026134A1
Polyethylene compositions
WO2021026135A1
Multilayer films that include at least five layers and methods of producing the same
WO2021026139A1
Polyethylene compositions and films including polyethylene compositions
WO2022005533A1